2006
DOI: 10.1161/circulationaha.105.595918
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Linked Kinase, a Hypoxia-Responsive Molecule, Controls Postnatal Vasculogenesis by Recruitment of Endothelial Progenitor Cells to Ischemic Tissue

Abstract: Background-Recruitment and adhesion of endothelial progenitor cells (EPCs) to hypoxic endothelial cells (ECs) isessential for vasculogenesis in ischemic tissue; little is known, however, about the key signals or intracellular signaling pathways involved in orchestrating the expression of adhesion molecules by ECs in response to hypoxia and how this is related to the recruitment of EPCs to the ischemic tissue. Here, we report that endogenous integrin-linked kinase (ILK) is a novel molecule that responds to hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 32 publications
(36 reference statements)
3
67
1
1
Order By: Relevance
“…Increased expression of SDF-1 in human and rodent models of infarcted myocardium has been confirmed by several studies [14][15][16][17]. SDF-1 expression was increased as early as 1h after induction of hypoxia in the myocardium or hindlimbs, suggesting a role in the initiation of tissue repair and revascularization [13,18,19]. Taken together, these data suggest that induction of SDF-1 by hypoxia provides an effective means to recruit circulating cells into neo-angiogenic niches.…”
Section: Expression Of Sdf-1 In Hypoxic Tissuesmentioning
confidence: 55%
See 1 more Smart Citation
“…Increased expression of SDF-1 in human and rodent models of infarcted myocardium has been confirmed by several studies [14][15][16][17]. SDF-1 expression was increased as early as 1h after induction of hypoxia in the myocardium or hindlimbs, suggesting a role in the initiation of tissue repair and revascularization [13,18,19]. Taken together, these data suggest that induction of SDF-1 by hypoxia provides an effective means to recruit circulating cells into neo-angiogenic niches.…”
Section: Expression Of Sdf-1 In Hypoxic Tissuesmentioning
confidence: 55%
“…Ceradini et al have demonstrated that SDF-1 expression in ischemic sites is directly correlated with the amplitude of hypoxia [12]. Signaling activated by hypoxia leading to SDF-1 upregulation involves the recruitment of integrin-linked kinase and hypoxia-inducible factor-1 (HIF-1) [12,13]. Increased expression of SDF-1 in human and rodent models of infarcted myocardium has been confirmed by several studies [14][15][16][17].…”
Section: Expression Of Sdf-1 In Hypoxic Tissuesmentioning
confidence: 97%
“…to significantly upregulate SDF1 (Cxcl12) expression in human ECs (33). Because we established that hasTF, and now masTF, ligate integrins, these TF variants could well trigger ILK-dependent signaling in murine ECs.…”
Section: N O N P R O T E O L Y T I C P R O P E R T I E S O F M U R I mentioning
confidence: 94%
“…Other models of neointimal formation have reported similar results, including balloon catheter carotid injury, where a decrease in ILK has been reported at the media layer, and re-expression at the luminal surface may attenuate this process during later stages of the injury response. 13 Additional examples include ablation of ILK in cultured endothelial cells, resulting in defective cell spreading, or progenitor endothelial cells lacking ILK which lead to defective vasculogenesis and embryonic lethality between E8.5 and E12.5, 37 whereas, in the adult, the absence of ILK produced endothelial dysfunction. 6 Despite the relevant role of ILK in the cardiovascular system, the mechanism of ILK stability has not been studied in detail.…”
Section: Discussionmentioning
confidence: 99%